FEATURES OF HEMORRHAGIC FEVER WITH RENAL SYNDROME AMONG CHILDREN POPULATION OF THE PRIMORSKI KRAI - O. V. Iunikhina; G. G. Kompanets (Acta Biomedica Scientifica, 2018)
Hemorrhagic fever with renal syndrome is a widespread natural-borne infection of orthohantavirus etiology in the territory of the  Russian Federation. Male patients of working age dominated, which  is associated with their professional and social activity. Although the  rate of children among all cases of this infection in our country is 2.5 %, the variety of clinical symptoms causes the problem in the diagnostic of this disease.The purpose of this work was to study the characteristics of  orthohantavirus infection among children and adolescents of  Primorski Krai.Materials and methods. A retrospective analysis of 60 serologically confirmed cases of orthohantavirus infection in children and  adolescents was carried out. Patients were divided into age  subgroups with a link to the possibility of infection in the urban or rural locations.Results. The prevalence of men aged 15-17 years among all studied patients was established. However, children starting from 3 years old are at risk of infection in rural areas of the region too, which is  related to proximity of natural landscapes. Circulation in the  Primorski Krai of two pathogenic orthohantaviruses (Hantaan and  Seoul) causes yearround registration of human orthohantavirus infection, including children.Conclusion. The Primorski Krai is an endemic territory for orthohantavirus infection, with the simultaneous circulation of  several orthohantaviruses. Risk of infection within all categories of  the population, including children, in whom the disease can occur  more often in a moderate form and with variety of different  symptoms, is related with the activation of the epizootic process in the rodent’s populations.